Nurses' Perceptions of Implant Barcode Scanning in Surgical Services. Issue 3 (March 2020) - Wilson, Natalia; Jehn, Megan; Kisana, Haroon; Reimer, Donada; Meister, Diane; Valentine, Kimberly; Reiser, Mark; Clarke, Henry
Abstract : The US Food and Drug Administration's 2013 Unique Device Identification System Rule requires manufacturers to label devices with unique identifiers. Implantable devices are now shipped with unique identifiers, and many electronic health records have fields to incorporate them. Health policy changes have prompted hospital systems to assess implementation of implant barcode scanning systems to capture unique device identifiers. Project aims were to assess predictors of operating room nurses' acceptance of a new implant barcode scanning system, describe operating room nurses' perceptions of the system value, and identify operating room nurses' perceived gaps in system implementation. An online survey was disseminated to operating room nurses, and focus groups were conducted with orthopedic operating room nurses in an academic medical center that had recently implemented an implant barcode scanning system in surgical services. Predictors of barcode scanning acceptance included perceived usefulness for patient care, perceived ease of use, and perceived usefulness (self). Nurses perceived the system to be more accurate and valuable for patient safety. Perceived gaps in system implementation related to communication, completeness of the system, consistency in process, and training. Understanding nurse perceptions of new barcode scanning systems and engaging them in the implementation process are key areas for success and optimization of these systems.